Analysis of periodic wave soliton structure for the wave propagation in nonlinear low–pass electrical transmission lines through analytical technique - Mujahid Iqbal; Jianqiao Liu; Aly R. Seadawy; Huda Daefallh Alrashdi; Reem Algethamie; Abeer Aljohani; Ce Fu (Ain Shams Engineering Journal)
In the present research, the nonlinear electrical equation named low–pass electrical transmission lines (LPETLs) equation under examination through extended simple equation approach. The nonlinear LPETLs model having important implications in sciences and engineering such as communication and electronic engineering included system of signal distribution in cable television, connection system of radio receiver and transmitter and its antennas, computer networking connected system, routing call truck lines of telephone switching centers, high speed data buses in computers and many others. In the presenting research, we examined novel solitons with interesting structure such as periodic wave solitons, kink wave solitons, bright solitons, anti–kink wave solitons, dark solitons, mixed bright and dark solitons, periodic traveling and solitary waves. The physical structure of some explored results demonstrated by contour, two–dimensional and three–dimensional through numerical simulation with computational Mathematica software. These novel explored results prove that proposed approach in this research is more straightforward, effective, not difficult to use and efficient to the investigation of different nonlinear differential equations.